SYNTHESIS, CHARACTERIZATION AND BIOLOGICAL EVALUATION OF 4-NITRO SCHIFF BASES - B.N.B.VAIDEHI,; K.SURYA TEJASWI,; N.V.PRABHAKAR,; L.DEVI, (International Journal of Pharma and Bio Sciences, 2013)
The purpose of the research was to synthesize better antibacterial and antioxidant compounds using various substituted aromatic aldehydes for synthesis of 4-Nitro Schiff bases in the presence of glacial acetic acid as catalyst. The synthesized compounds were screened for antioxidant activity by DPPH method and antibacterial activity by Cup Plate method. The antibacterial activity was evaluated against four bacterial strains. IR spectroscopy and elemental analysis were used for characterization of compounds. Some of the synthesized compounds exhibited promising antioxidant and antibacterial activities.